Analisis Pengaruh Perbedaan Diameter Dalam Terhadap Efisiensi Turbin Ulir Archimedes - Habibi, Muhammad Iqbal; Asral, Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Among renewable energy sources, energy from water in small scale water power plants much in demand because the operation is cheap, clean and environmentally friendly. Especially in low head, this type of power plants becomes the best choice for electrifying remote area in developing country and one of the best type is screw turbine. In this study the author will discusses the effect of differences inner diameter of screw turbine on the efficiency of the Archimedes turbine. This experiment using two variations of the ratio of the inner diameter to the outer diameter which is 0.1Do and 0.5Do at turbine length 0.9 m and outer diameter 0.25m and pitch 2Ro (the turbine length, outer diameter and pitch both turbine are equal). This experiment using variety of water flow discharge from 1.35 – 0.09 l/s and variety of angle of inclination of the turbine from 0o – 60o (with the addition of angle by 10o). This test is carried out to determine the efficiency of both turbine. The result of this experiment indicating the most efficiency achieved by turbine witch inner diameter 0.5Do which is 15.71% and followed by inner diameter 0.1Do is 6.85%. The most efficiency of the both turbine obtained on angle of inclination 40o and flow discharge 0.8 l/s. Keywords: Screw turbine, inner diameter, flow discharge, angle of inclination, efficiency